IMPLEMENTASI TEKNOLOGI DIGITAL PUBLIC RELATIONS DALAM MANAJEMEN HUBUNGAN MASYARAKAT PENDIDIKAN - Silvia, Nela; Susanto, Edi; Annisa, Siti; Juniarti, Vevi; Yulianti, Feni; Parizal; Basroh, Muhammad Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation has significantly reshaped public relations practices in educational institutions, shifting communication from conventional approaches to more open, interactive, and technology-based engagement. This development encourages educational institutions to optimize digital technologies in establishing effective relationships with various stakeholders. This study aims to analyze the implementation of digital technology in educational public relations management, identify its benefits and challenges, and synthesize previous research findings using the PESO (Paid, Earned, Shared, and Owned Media) Model as the analytical framework. This research employed a library research approach with a qualitative descriptive method. Data were collected from scientific journal articles published between 2016 and 2026 through Google Scholar, Garuda, SINTA, and ResearchGate, and were analyzed using content analysis and thematic synthesis techniques. The findings indicate that the implementation of digital technology in educational public relations is primarily characterized by the integrated use of websites, social media platforms, and instant messaging applications. These digital platforms contribute to improving communication efficiency, accelerating responses to public information needs, and increasing parental and community engagement. However, several challenges remain, including the digital divide, limited human resource competencies, and inadequate digital literacy. Based on the PESO Model analysis, digital public relations practices in educational institutions are still predominantly focused on owned media and shared media, while the utilization of earned media and paid media remains relatively limited. Therefore, educational institutions need to develop more integrated digital public relations strategies to enhance communication effectiveness, strengthen institutional reputation, and foster sustainable relationships with stakeholders.